An investigation of the effectiveness of the division of corporate finance as a monitor of financial reporting. Issue 1 (April 2017) - Edmonds, Jennifer E.; Leece, Ryan D.
Abstract: This study investigates whether the Securities and Exchange Commission's Division of Corporate Finance (DCF) allocates resources toward public companies that investors perceive as having poor financial reporting quality. Resource allocation within the DCF is an important topic given the SEC's overall mission to improve disclosures and protect investors. The findings are consistent with the DCF being more likely to allocate resources toward firms that market participants perceive as having poor financial reporting quality.